NEW CYTOTYPES OF PTERIS ENSIFORMIS VAR. VICTORIAE FROM INDONESIA - Efendi, Muhammad; Chikmawati, Tatik; Darnaedi, Dedy (Research Center for Biology, 2014)
New cytotypes of Pteris ensiformis var. victoriae and one cytotype of var. ensiformis are recorded from Indonesia: var. victoriae with 2n=58 (sexual diploid) from Gorontalo, North Sulawesi, and 2n=87 (triploid) from Lombok Island and Bogor, West Java; and var. ensiformis with 2n=116 (sexual tetraploid). The diploid is smaller than the triploid in plant size. Results indicate a cytological variation in var. victoriae, like in var. ensiformis.